Peningkatan Kualitas Pelayanan Pengambilan Gaji Pensiun Asabri di PT Pos Indonesia Cabang Krembangan - Firda Nur Salsabila; Ira Wikartika (Pusat Riset dan Inovasi Nasional, 2026)
The disbursement service for Asabri pension salaries at PT Pos Indonesia, Krembangan Branch, experiences an increase in visitor numbers at the beginning of each month, resulting in crowded queues and the need for faster, clearer, and easier-to-understand service for pensioners. Most of the service recipients are elderly individuals who have limitations in reading information or following authentication procedures, making direct assistance highly necessary. This community service activity was conducted to gain a real understanding of the service flow, identify the main challenges faced by pensioners, and observe how the presence of internship students can help streamline the process. The methods used included observation, service assistance, and interviews with staff. The results show that many pensioners still require support, especially in the authentication process and understanding the queue flow. The presence of students was proven to help speed up service, reducing the average service time from 4 minutes to 2.5 minutes per person and making the queue flow more orderly. In addition to improving efficiency, the assistance also had a positive impact on the comfort of pensioners, as they received simpler explanations and direct help when facing difficulties. Therefore, this activity demonstrates that friendly, responsive, and elder-sensitive service is key to improving service quality for pensioners at PT Pos Indonesia, Krembangan Branch.